The most common congenital malformations in dogs: Literature review and practical guide - Estevam, Marina Vilela [UNESP]; Toniollo, Gilson Helio [UNESP]; Apparicio, Maricy [UNESP] (Elsevier, 2024)
Congenital malformations can affect almost 7% of canine newborns. The increase of commercial dog breeding and inbreeding used to maintain the striking characteristics of each breed, the appearance of malformations has become increasingly common, especially in brachycephalic dogs. The causes are diverse, and include genetic, nutritional, iatrogenic, and infectious factors, often making it difficult to establish a cause-consequence relationship. The high mortality associated with malformations comes not only from the fact that some are incompatible with life, but also because even if many undergo surgical treatment or correction, they require specific management, monitoring, and clinical treatment for an indefinite period of time. The most common malformations such as cleft lip and palate, hydrocephalus and anasarca have been studied for a long time, and it is currently known that brachycephalic dogs have a greater predisposition, however, for other less common conditions as gastroschisis and hypospadias, there is only a few case reports. The appearance of congenital defects in a litter leads to financial losses for the breeder, emotional losses for the owner and the veterinarian and harms the well-being of that individual. For this reason, the aim of this review article is to gather relevant information on the characteristics, diagnosis, and management of the main malformations in puppies. It is essential that the veterinarian is prepared to diagnose and treat these conditions, reducing negative impacts on animals and owners.
Keywords: Birth defects; Canine; Fetal anomaly; Newborn abnormality